Keynes versus the post keynesians on the principle of effective demand - Jochen Hartwig (ETH Zurich, KOF Swiss Economic Institute, 2004)
The American Post Keynesians - those who attach importance to the Big P and the absence of a dash between post and Keynesian - claim to be Keynes's most literal interpreters, or the truest Keynesians (HOLT ET AL., 1998, p. 17). This paper compares the Post Keynesian interpretation of the Principle of Effective Demand, i.e. the D/Z-model, with Keynes's own presentation in Chapter 3 of the General Theory - and finds substantial differences. A reinterpretation of the D/Z-model is offered that would bring it into line with Chapter 3.
Keywords: B22; E12; E20; E31; 330; Effective demand; D/Z-model; Gesamtwirtschaftliche Nachfrage; Postkeynesianismus; Keynesianismus